2003
DOI: 10.1182/blood-2003-01-0123
|View full text |Cite
|
Sign up to set email alerts
|

Double jeopardy from a single translocation: deletions of the derivative chromosome 9 in chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) is characterized by formation of a BCR-ABL fusion gene, usually as a consequence of the Philadelphia (Ph) translocation between chromosomes 9 and 22. Recently the development of new fluorescence insitu hybridization (FISH) techniques has allowed identification of unexpected deletions of the reciprocal translocation product, the derivative chromosome 9, in 10% to 15% of patients with CML. These deletions are large, span the translocation breakpoint, and occur at the same time as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
1
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 108 publications
5
74
1
3
Order By: Relevance
“…6 This technique allows for the detection and (where metaphases are present) location of both the BCR/ABL and ABL/BCR fusion genes. 7 In cells with a deletion, one or both of the signals corresponding to ABL/BCR are absent from the der (9). These findings were correlated with molecular studies indicating loss of the ABL/BCR fusion transcript in a number of patients.…”
Section: Introductionsupporting
confidence: 71%
“…6 This technique allows for the detection and (where metaphases are present) location of both the BCR/ABL and ABL/BCR fusion genes. 7 In cells with a deletion, one or both of the signals corresponding to ABL/BCR are absent from the der (9). These findings were correlated with molecular studies indicating loss of the ABL/BCR fusion transcript in a number of patients.…”
Section: Introductionsupporting
confidence: 71%
“…These systems are equivalent, except in their ability to detect deletions of chromosome 22 sequences in addition to deletions of sequences from the derivative chromosome 9. 31 In this regard, deletions solely of chromosome 22 sequences may have been missed in the 53 patients analyzed with the ES probe system. The rates of CHR, MCR, and CCR achieved in patients according to deletion status and disease phase are shown when available.…”
Section: Discussionmentioning
confidence: 99%
“…The second possibility is that the size of the cohort of newly diagnosed patients is simply too small to show any differences. The presumed molecular mechanism underlying the deletions is loss of a tumor suppressor gene, 31 and, because of the heterogeneity of the size and type (chromosome 9 and/or 22 sequence loss) of deletions, it is likely that only a subgroup of patients with deletions actually carry this molecular lesion. However, the third explanation is that the molecular lesion associated with deletion of derivative chromosome 9 sequences may require time to irrevocably drive disease progression, irrespective of imatinib treatment, and however early it is started.…”
Section: Discussionmentioning
confidence: 99%
“…The most probable hypothesis is that microdeletions could be associated with the loss of tumor suppressor genes or genes implicated in cell-cycle regulation, resulting in a proliferative advantage of the leukemic clone. 4 This phenomenon may act by a gene dosage effect known as haploinsufficiency: mutation or loss of a single allele may be sufficient to elicit a cellular phenotype that leads to tumorigenesis without the inactivation of the second allele. The aim of our study was therefore to assess whether the sequences loss on der(9) in CML patients was associated with a gene product decrease.…”
mentioning
confidence: 99%
“…To study these differences in the expression profiles of leukemic cells, we selected 26 genes (5 genes from Staal et al 3 and 21 top-ranked genes from Beesley et al 4 ) that showed differential expression in diagnosis and relapse, originating from the above-mentioned studies that compared gene expression levels between diagnosis and relapse in B-precursor ALL.…”
mentioning
confidence: 99%